Aggiornamento? : Catholicism from Gregory XVI to Benedict XVI - Schelkens, Karim (Brill's series in church history ;, 2013)
Fifty years after Vatican II, the time has arrived to relocate this council against a broad horizon. Therefore, this volume offers a survey of the evolution of Catholicism, from ca. 1830 to the present-day, tying together the renewals proposed by the first and the Second Vatican Councils.